La maturità di INSPIRE - Salvemini, Mauro (GEOmedia, 2010)
INPIRE's maturity The INSPIRE Conference 2010 took place from 23 to 25 June 2010 in Kraków, Poland. On 22 June pre-conference workshops have been organized. The theme of this year's edition has been "INSPIRE as a Framework for Cooperation". The INSPIRE Conference has been organised through a series of plenary sessions addressing common policy issues, and parallel sessions focusing in particular on applications and implementations of SDIs, research issues and new and evolving technologies and applications and poster presentations.